Emerging microbial intervention technologies and innovations for enhanced food quality and safety from a Halalan Toyyiban perspective and One Health approach - Al-Saari, Nurhidayu; Abdullah Sani, Wardini; Ahmad Azmi, Nur Sabrina; Fujiyoshi, So; Maruyama, Fumito (Springer, 2024)
High-profile foodborne illness outbreaks necessitate immediate collaborative efforts on the part of industry, regulators, and researchers to improve food safety tactics and technologies utilised throughout the food supply chain. The health of humans, animals, and the ecosystem as a whole is now intricately intertwined and interdependent due to the new dynamic brought about by their convergence. At its best, globalization of the food supply has further increased the emergence, re-emergence, and spread of food-borne pathogens, demanding a more robust farm-to-fork food safety framework that includes microbial intervention technologies. This chapter delves into the intricate landscape of food safety within the framework of Halalan Toyyiban principles and a One Health approach. Focusing on emerging microbial intervention technologies, the discussion explores the dissemination of food-borne diseases, presenting a comprehensive overview of innovations, trends, and the evolving dynamics in this critical domain. Additionally, the chapter examines the opportunities and challenges inherent in the development and implementation of microbial interventions, shedding light on the pivotal role these interventions play in enhancing food quality and safety. By embracing a One Health perspective, the chapter provides insights into effectively managing disease outbreaks and their dissemination, offering a holistic understanding of the interconnectedness between human, animal, and environmental health.